Análisis del uso de Facebook a nivel municipal. Una aplicación a municipios españoles - Bonsón, Enrique; Royo, Sonia; Cambra, Esther (Revista del CLAD Reforma y Democracia, 2018)
AbstractThe use of social networks and other Web 2.0 tools has gained great importance in the public sector since it enables a new form of communication between the administration and the citizens. Appropriate metrics and methodologies are needed to determine its impact. This work illustrates the application of different metrics of Facebook use at the municipal level, both by city councils and citizens, taking a sample of Spanish councils and public data. The results show that a considerable percentage of city councils do not use Facebook to communicate with the citizens. Also, municipalities that use Facebook reach modest levels of awareness and interaction and don’t use the media or content that generates the most impact on users. Therefore, local administrations must rethink their strategies regarding the use of these tools to improve their interaction with the citizens.
Keywords: Redes Sociales Digitales; Análisis de Redes; Participación Ciudadana; Relaciones con los Administrados; Municipalidades; España